Formation of charge-nanopatterned templates with flexible geometry via layer by layer deposition of polyelectrolytes for directed self-assembly of gold nanoparticles - Sayın, Mustafa; Dahint, Reiner (Nanotechnology, 2017)
Nanostructure formation via self-assembly processes offers a fast and cost-effective approach to generate surface patterns on large lateral scale. In particular, if the high precision of lithographic techniques is not required, a situation typical of many biotechnological and biomedical applications, it may be considered as the method of choice as it does not require any sophisticated instrumentation. However, in many cases the variety and complexity of the surface structures accessible with a single self-assembly based technique is limited. Here, we report on a new approach which combines two different self-assembly strategies, colloidal lithography and layer-by-layer deposition of polyelectrolytes, in order to significantly expand the spectrum of accessible patterns. In particular, flat and donut-like charge-patterned templates have been generated, which facilitate subsequent deposition of gold nanoparticles in dot, grid, ring, out-of-ring and circular patch structures. Potential applications are e.g. in the fields of biofunctional interfaces with well-defined lateral dimensions, optical devices with tuned properties, and controlled three-dimensional material growth.
Gesehen am 11.09.2018